DAMPAK SERTIFIKASI DAN STANDARDISASI PRODUK DALAM PENINGKATAN PENJUALAN DAN DAYA SAING UMKM - Nur Anita; Muhammad Luthfi Iznillah, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
This study aims to determine the impact of certification and standardization of MSME products fostered by CSR PT Pertamina RU II Sei Pakning in increasing sales and competitiveness of MSMEs. This research is a qualitative research with descriptive method, data collection technique is done by using In Depth Interview. There are 5 representatives of business groups who are respondents in this study. The results show that certification and standardization have a strong enough impact in increasing sales and competitiveness of MSMEs. Therefore, it is important for every business actor to have product certification and carry out standardized production and operational processes in order to realize sustainable improvements which are then able to make MSMEs survive in the long term.